(untitled) (Journal of Forensic Medicine & Toxicology, 2022)
Being a part of particular treatment modality must be decision of patient. To provide better preventive, curative, palliative and holistic care to patients, curriculum for under graduate doctors being updated from time to time as required. National Medical Commission, Under Graduate Medical Board, India has upgraded rules and regulations for compulsory rotating internship 2021. Such new provision has been introduced where MBBS intern doctors can choose elective exclusive posting in one of the disciplines of Indian Systems of Medicine which include Ayurveda, Siddha, Unani,Yoga, Sowa Rigpa and Homoeopathy. To know the perspective of MBBS intern doctors, this cross sectional observational study was conducted at Parul Institute of Medical Sciences, Parul University, Vadodara, India. Study among 150 interns revealed that most of themwere not having enough awareness about various disciplines of Indian systems of medicine. However most of the intern doctors have welcomedsuch integration in internship postings. Majority of intern doctors stated that usefulness of other modalities of Indian System of Medicine in treating chronic illnesses can not be ruled out as an alternative choice by the patient. Majority stated that modern allopathic treatment would have exclusive dominant role in emergencies. Overall intern doctors opined that they want to learn more about various other disciplines of Indian Systems of Medicine which will be helpful to their clinical practice, beneficial to patients and ultimately contribute to health care as well.